Investigating systematic review for multi-disciplinary research in the built environment. Issue 1 (5th February 2018) - Parida, Subhadarsini; Brown, Kerry
Abstract : Purpose: The purpose of this paper is to examine the extent to which a systematic review approach is transferable from medicine to multi-disciplinary studies in the built environment research. Design/methodology/approach: Primarily a review paper, it focuses on specific steps in the systematic review to clarify and elaborate the elements for adapting an evidence base in the built environment studies particular to the impact of green building on employees' health, well-being and productivity. Findings: While research represents a potentially powerful means of reducing the gap between research and practice by applying tried and tested methods, the methodological rigour is debatable when a traditional systematic review approach is applied in the built environment studies involving multi-disciplinary research. Research limitations/implications: The foundational contribution of this paper lies in providing methodological guidance and an alternative framework to advance the longstanding efforts in the built environment to bridge the practitioner and academic divide. Originality/value: A systematic review approach in the built environment is rare. The method is unique in multi-disciplinary studies especially in green building studies. This paper adopts the systematic review protocols in this cross-disciplinary study involving health, management and built environment expertise.